2020
DOI: 10.1016/j.biomaterials.2019.119634
|View full text |Cite
|
Sign up to set email alerts
|

Cell-mediated matrix stiffening accompanies capillary morphogenesis in ultra-soft amorphous hydrogels

Abstract: There is a critical need for biomaterials that support robust neovascularization for a wide-range of clinical applications. Here we report how cells alter tissue-level mechanical properties during capillary morphogenesis using a model of endothelial-stromal cell co-culture within poly(ethylene glycol) (PEG) based hydrogels. After a week of culture, we observed substantial stiffening in hydrogels with very soft initial properties. Endothelial cells or stromal cells alone, however, failed to induce hydrogel stif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 51 publications
2
15
0
Order By: Relevance
“…However, control of dynamic reciprocity between cell and matrix may sidestep these drawbacks and lead to more biomimetic, instructive local niches for better biological responses to percutaneous devices [ 505 , 506 ] Degradability, stress relaxation, stiffness, morphology, etc. are potential routes of achieving control of pericellular matrix features, such as structure and/or contents [ [507] , [508] , [509] ]. Moreover, material surface properties in particular have begun to be harnessed to control nascent matrix structure [ 510 , 511 ] and differential activation of rigidity sensing pathways [ 512 ].…”
Section: Future Perspectives and Avenues For Innovation And Inspirati...mentioning
confidence: 99%
“…However, control of dynamic reciprocity between cell and matrix may sidestep these drawbacks and lead to more biomimetic, instructive local niches for better biological responses to percutaneous devices [ 505 , 506 ] Degradability, stress relaxation, stiffness, morphology, etc. are potential routes of achieving control of pericellular matrix features, such as structure and/or contents [ [507] , [508] , [509] ]. Moreover, material surface properties in particular have begun to be harnessed to control nascent matrix structure [ 510 , 511 ] and differential activation of rigidity sensing pathways [ 512 ].…”
Section: Future Perspectives and Avenues For Innovation And Inspirati...mentioning
confidence: 99%
“…In this case, noted material complexities corresponding to the cell behavior involved the stiffness of the material itself, as well as its degradability. [204] While certain applications require global alterations to the entire composite, changes related to superficial and surface characteristics may be more appropriate in other cases. One such example demonstrated by Heyde and Ruder involved linking a biomaterial surface with genetically engineered E. coli meant to upregulate biotin production in the presence of isopropyl β-d-1-thiogalactopyranoside (IPTG); this served as a means of regulating the surface's ability to undergo binding via streptavidin-biotin interactions.…”
Section: Modulation Of Composite Characteristics and Propertiesmentioning
confidence: 99%
“…[221] This strategy may also be found in other methods which have attempted to use cell-driven regulation of matrix stiffness in order to modulate vasculogenesis. [204,222] Rüdiger et al recently demonstrated such a process in engineering an endothelial tube across a Matrigel membrane. As starting material complexities, the topology, stiffness, and connectivity of the surrounding matrix exerted significant influence over initial cellular events leading to selforganization.…”
Section: Converging Materials and Biological Complexitymentioning
confidence: 99%
See 1 more Smart Citation
“…To fulfill the demand in the medical field, research on constructing a tissue having such 3D structure in vitro has been actively conducted in order to form a model as similar as possible to the living body [ 4 ]. Numerous studies on fabrication techniques of blood capillary models have been reported, such as bio-printing, organ-on-chip or microfluidic device, electrospinning techniques, cells sheet, as well as scaffold structure [ 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. However, some problems remain, such as the inability to control of the geometry of the three-dimensional arrangement or the biocompatibility: even in 3D bioprinted scaffolds it is still difficult to precisely tune their endothelialization after adding the cells and some synthetic vascular grafts for clinical application were found to be associated with thrombosis, aneurysm, and intimal hyperplasia occurrence due to their lack of compliance (possibility to strain/expanse or contract) [ 12 ].…”
Section: Introductionmentioning
confidence: 99%